Adsorption of Cu(Ii) Ions in Aqueous Solution Onto Limonia Acidissima Shellbased Activated Carbon: Kinetic and Isotherm Studies - Muslim, Abrar; Said, Syahiddin Dahlan; Hariati, Gita Suci; Karina, Siti Fajar; Djuned, Fauzi Muhammad; Mulyawan, Rizka (UI Scholars Hub, 2017)
Adsorption of Cu(II) ions from aqueous solution using activated carbon prepared from Limonia acidissima fruit shell (LAFS-AC) was conducted in batch mode experiments at pH 5 (±0.15), 100 rpm and 1 atm. The effects of contact time, initial Cu(II) ions concentration, KOH concentration, and adsorption temperature on Cu(II) ions adsorption capacity were investigated. Fourier Transform Infrared Spectroscopy and Scanning Electron Microscopy analyses were performed to investigate the active site and surface morphology of the LAFS-AC, respectively. The Cu(II) ions adsorption was fitted very well (R2 = 0.94 on average) to the pseudo second-order adsorption kinetic with the adsorption capacity and rate being 25.58 mg/g and 0.07 g/mg.min, respectively at 27 oC by the LAFS AC activated using 0.5 M KOH. It was 26.88 mg/g and 0.15 g/mg.min, respectively at 60 oC. The Cu(II) ions adsorption followed the Langmuir adsorption isotherm model (LAIM) (R2 = 0.98 on average). The LAIM adsorption capacity and constant were 26.67 mg/g and 0.03 L/g, respectively at 27 oC. It increased dramatically to 0.09 L/g at 60 oC. The optimal adsorption condition obtained was the 0.5 M KOH activated LAFS-AC, initial Cu(II) concentration of 509.81 mg/L and 120-min contact time at 60 oC with the Cu(II) ions adsorption capacity of 26.95 mg/g.